Analysis of The Implementation of Organizational Culture, Internal Control Systems, Implementation of Good Corporate Governance Principles, and Their Impact on The Quality of Financial Reports - Ahmad Suhemi; Hari Setiyawati (LPPM Universitas Trunojoyo Madura, 2023)
This research begins with a phenomenon where fraud is related to the principles of Good Corporate Governance that are not implemented properly by the company. The low level of employee discipline towards organizational culture and the low internal control system are used as an opportunity to cheat by taking advantage of position and position. If these two things are carried out properly, the company can minimize fraud, which can affect the quality of reports. Here the researcher uses a quantitative approach through causal research. The population chosen by researchers is manufacturing companies in the consumer goods industry sector listed on the IDX in the 2021 period. The research sample used the accidental sampling method, comprising 64 manufacturing companies in the consumer goods industry sector and 85 respondents. The process of collecting primary data by utilizing a questionnaire. Data analysis and processing apply Smart PLS. His research proves that the internal control system has a significant positive influence on the principles of good corporate Governance but does not affect the quality of financial reports. Meanwhile, organizational culture significantly positively affects the principles of Good Corporate Governance and the quality of financial reports. The principles of Good Corporate Governance significantly positively affect the quality of financial reports.